Flex-Faso exporting green beans from Burkina Faso - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Flex-Faso exemplifies the success which can be achieved when African export companies pay careful attention to quality control and train their growers and handlers alike to give European consumers what they want. Flex-Faso is a broadly based...